Application of extracellular vesicles proteins in cancer diagnosis - Huang, Defa; Rao, Dingyu; Xi, Xuxiang; Zhang, Zuxiong; Zhong, Tianyu (Frontiers in Cell and Developmental Biology, 2022)
Early tumor diagnosis is crucial for its treatment and reduction of death, with effective tumor biomarkers being important tools. Exosomes are small vesicles secreted by cells with various biomolecules, including proteins, nucleic acids, and lipids. They harbor a double membrane structure. Previous studies on exosomes in cancer diagnosis and therapy focused on miRNAs. Nonetheless, exosomes contain proteins that represent physiological and pathological state of their parental cells. Exosome proteins can reflect the pathological state of some diseases, which provides a basis for diagnosis and treatment. This study describes the role of exosomes in cancer and summarizes the use of exosomal proteins as diagnostic markers in different cancer types. Specifically, we discuss the potential and shortcomings of exosomes as tumor biomarkers.